Performance enhancement in the workplace: why and when healthy individuals should disclose their reliance on pharmaceutical cognitive enhancers - Garasic, Mirko D.; Lavazza, Andrea (Frontiers in Systems Neuroscience, 2015)
The use of pharmaceuticals cognitive enhancers (PCE) have been stirring growing interest, not only in the scientific domain but also in the popular media, and has probably had some increase recently in academic, professional and military quarters, although such increase is very difficult to assess. In line with an attitude of general acceptance towards – at least some of – the practical implementations of Human Enhancement (HE), this phenomenon is deemed as a normal procedure aimed at improving the performance of an individual as well as the overall standards of an organization. Although the vast majority of countries have some kind of restrictions to reduce the wide non-medical usage of PCE, these can be overcome quite easily. Our main objective in this theoretical paper is to underline the tension between the bio-liberal motto “the use of PCE is a freely eligible personal choice”, and the practical context in which its “secret” or concealed implementation might lead to potential dysfunctional or dangerous interpersonal or social consequences.